Higher emotion regulation flexibility predicts more stable negative emotions and faster affective recovery in early psychosis: an experience sampling study - Li, Xu; Vaessen, Thomas; Lafit, Ginette; Aubel, Evelyne van; Hiekkaranta, Anu P.; Houben, Marlies; Beijer-Klippel, Annelie; Haan, Lieuwe de; Schirmbeck, Frederike; Reininghaus, Ulrich; Myin-Germeys, Inez (Psychological medicine, 2024)
While evidence shows that people with early psychosis are flexible in using different emotion regulation (ER) strategies to manage the varying contextual demands, no studies have examined the effectiveness of such regulatory flexibility in this population. We addressed this issue by investigating whether and how ER flexibility relate to different dynamic aspects (variability, instability, inertia, and recovery) of negative affect (NA) in a combined early psychosis sample, consisting of both individuals at high clinical risk for psychosis and those diagnosed with first-episode psychosis. - Participants were 148 individuals from the INTERACT project, a multi-center randomized controlled trial on the efficacy of acceptance and commitment therapy in early psychosis. We utilized data from the baseline assessment, during which all participants completed six days of experience sampling assessment of momentary NA, as well as end-of-day assessments of ER strategy use. - Multilevel models of within-person associations showed that greater ER flexibility was associated with more stable NA, and quicker recovery of NA from stressors during the day. Linear regression analyses of between-person associations showed that people who had more variable and unstable NA reported greater ER flexibility generally. No evidence was found for associations with NA inertia. - The current study identified unique within-person and between-person links between ER flexibility and dynamics of NA in early psychosis. These findings further provide evidence for ER flexibility in early psychosis, emphasizing the adaptive nature of regulatory flexibility in relation to reduced instability in NA and faster recovery from NA in everyday life.
Online verfügbar: 12. Februar 2024
Gesehen am 29.10.2024